If the equation is: y = -x then the slope is -1 and there is no y intercept
4
y-x is an expression, not an equation. Therefore, the question does not make sense.
-- Take the equation. -- Say to yourself, "At the x-intercept, y=0". Set 'y' equal to zero, solve the equation for 'x', and you have the x-intercept. -- Take the original equation again. -- Say to yourself, "At the y-intercept, x=0". Set 'x' equal to zero, solve the equation for 'y', and you have the y-intercept.
Set x = 0 and solve the resulting equation in y for the y-intercept. Set y = 0 and solve the resulting equation in x for the x-intercept.
The equation y x - x a is an algebraic equation that many learn in school, which involves numbers as well as letters. The equation y x - x a would be x (y-1).
In mathematics, when we have an equation with two variables like y = f(x), we can find the value of y when x is three by substituting x = 3 into the equation. Without the specific equation provided, it is impossible to determine the value of y when x is three. The solution would depend on the function or relationship between y and x given in the equation.
If y = y + x then x must be 0 Otherwise the equation is meaningless.
The 'x' and 'y' intercepts of that equation are both at the origin.
If you mean the slope of the line with equation y = x then it is 1 and there is no y intercept
If the equation is: y = -x then the slope is -1 and there is no y intercept
If you are solving for y, it is fine. If you are solving for x, divide both sides by x and the equation should be x = y/x
x = 2 and y = -4
4
y-x is an expression, not an equation. Therefore, the question does not make sense.
-- Take the equation. -- Say to yourself, "At the x-intercept, y=0". Set 'y' equal to zero, solve the equation for 'x', and you have the x-intercept. -- Take the original equation again. -- Say to yourself, "At the y-intercept, x=0". Set 'x' equal to zero, solve the equation for 'y', and you have the y-intercept.
Set x = 0 and solve the resulting equation in y for the y-intercept. Set y = 0 and solve the resulting equation in x for the x-intercept.